Integrasi Nilai Karakter Religius Siswa Melalui Pembiasaan Pembacaan Asmaul Husna di SD Supriyadi 02 Semarang - Septianingsih, Khoirunnisa; Azizah, Mira; Sofiati, Ranto Netty; Nuroso, Harto (Jurnal Penelitian Multidisiplin Ilmu, 2024)
This study aims to determine the process of implementing the habituation of reciting asmaul husna and the supporting factors of the process of implementing asmaul husna habituation, in order to instill the religious character of students at SD Supriyadi 02 Semarang. The type of research used is field research with a qualitative descriptive approach. The data collection method was carried out in three stages, namely: Observation, interview and documentation. While the data analysis techniques are: Data reduction, data presentation, and conclusion drawing. The results of this study found that: 1) The formation of students' religious character in SD Supriyadi 02 Semarang is carried out by habituation of reciting asmaul husna every morning before learning begins 2) Supporting factors in the formation of students' religious character in SD Supriyadi 02 Semarang are: with adequate facilities, diligent and consistent teachers.